Generation of Functional Inhibitory Synapses Incorporating Defined Combinations of GABA(A) or Glycine Receptor Subunits - Dixon, Christine L.; Zhang, Yan; Lynch, Joseph W. (Frontiers in Molecular Neuroscience, 2015)
Fast inhibitory neurotransmission in the brain is mediated by wide range of GABAA receptor (GABAAR) and glycine receptor (GlyR) isoforms, each with different physiological and pharmacological properties. Because multiple isoforms are expressed simultaneously in most neurons, it is difficult to define the properties of inhibitory postsynaptic currents mediated by individual isoforms in vivo. Although recombinant expression systems permit the expression of individual isoforms in isolation, they require exogenous agonist application which cannot mimic the dynamic neurotransmitter profile characteristic of native synapses. We describe a neuron-HEK293 cell co-culture technique for generating inhibitory synapses incorporating defined combinations of GABAAR or GlyR subunits. Primary neuronal cultures, prepared from embryonic rat cerebral cortex or spinal cord, are used to provide presynaptic GABAergic and glycinergic terminals, respectively. When the cultures are mature, HEK293 cells expressing the subunits of interest plus neuroligin 2A are plated onto the neurons, which rapidly form synapses onto HEK293 cells. Patch clamp electrophysiology is then used to analyze the physiological and pharmacological properties of the inhibitory postsynaptic currents mediated by the recombinant receptors. The method is suitable for investigating the kinetic properties or the effects of drugs on inhibitory postsynaptic currents mediated by defined GABAAR or GlyR isoforms of interest, the effects of hereditary disease mutations on the formation and function of both types of synapses, and synaptogenesis and synaptic clustering mechanisms. The entire cell preparation procedure takes 2 – 5 weeks.